2021
DOI: 10.3389/fpls.2020.611247
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Treatment but Not Green Light Treatment After Pre-exposure to UV-B Stabilizes Flavonoid Glycoside Changes and Corresponding Biological Effects in Three Different Brassicaceae Sprouts

Abstract: Ultraviolet-B (UV-B; 280–315 nm) radiation induces the biosynthesis of secondary plant metabolites such as flavonoids. Flavonoids could also be enhanced by blue (420–490 nm) or green (490–585 nm) light. Flavonoids act as antioxidants and shielding components in the plant’s response to UV-B exposure. They are shown to quench singlet oxygen and to be reactive to hydroxyl radical. The aim was to determine whether treatment with blue or green light can alter flavonoid profiles after pre-exposure to UV-B and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
0
13
1
Order By: Relevance
“…Nowadays, there is increasing consumer concern about the nutritional quality of food, as vegetable origin foods are key for a healthy diet. The role of these plant-based foods in the prevention of a wide array of chronic diseases is associated with their content in bioactive compounds (nutrients and non-nutrients), and to the modification of molecular pathways responsible for the onset and advance of pathophysiological processes [1,2]. Regarding this point, cruciferous sprouts have been demonstrated to be a source of valuable bioactive micronutrients (vitamins and minerals) and phytochemical compounds (glucosinolates and phenolics), related to the prevention of inflammatory, tumoral, or metabolic disorders [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is increasing consumer concern about the nutritional quality of food, as vegetable origin foods are key for a healthy diet. The role of these plant-based foods in the prevention of a wide array of chronic diseases is associated with their content in bioactive compounds (nutrients and non-nutrients), and to the modification of molecular pathways responsible for the onset and advance of pathophysiological processes [1,2]. Regarding this point, cruciferous sprouts have been demonstrated to be a source of valuable bioactive micronutrients (vitamins and minerals) and phytochemical compounds (glucosinolates and phenolics), related to the prevention of inflammatory, tumoral, or metabolic disorders [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the same matrix, the authors applied 24 or 36 h of 2 W m −2 UV-B (314 nm), which positively affected the isoflavone accumulation and the gen stimuli related to chalcone synthases, mainly related to the flavonoid biosynthesis [83]. When UV-B and coloured LEDs were combined, Neugart et al [59] showed that 99 µmol m −2 s −1 blue LEDs increased and stabilised the flavonoid content in kale, kohlrabi, and rocket sprouts, whereas 119 µmol m −2 s −1 green LEDs supplemented with UV-B 1.15 W m −2 did not. Gui et al [84] studied the use of UV-B daily treatments (0.7 W m −2 ) during the growth of mung bean sprouts and reported an inhibition of the microbial growth.…”
Section: Preharvest Uv and Visible Spectrum Illumination Strategies T...mentioning
confidence: 99%
“…Phenolic compounds were extracted from lyophilized crushed plant material. Extraction was carried out three times with a 60% (v/v) aqueous methanol solution [59]. The resulting combined extract was filtered and used to determine the total content of hydroxycinnamic acids, the total content of flavonoids, the total content of phenolic compounds, and for high-performance liquid chromatography (HPLC) analysis of individual phenolic compounds.…”
Section: Determination Of Phenolic Compoundsmentioning
confidence: 99%